2013
DOI: 10.1159/000346397
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Intraocular Pressure Changes in Patients with Neovascular Age-Related Macular Degeneration Treated with Ranibizumab

Abstract: Background/Aims: To investigate the long-term effects of multiple intravitreal injections (IVTs) of ranibizumab (Lucentis) on intraocular pressure (IOP) in patients with neovascular age-related macular degeneration. Methods: In 320 eyes, IOP measurements were performed at baseline prior to injection and compared with IOP measurements of the last visit. Correlations between mean IOP change and total number of IVTs, visual acuity or patient age were tested. Results: The mean IOP increase was 0.8 ± 3.1 mm Hg (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
4
18
0
1
Order By: Relevance
“…The use of intravitreal antiangiogenic agents has assumed increasing importance and worldwide application in various vitreoretinal pathologies. Recent evidence suggests that both short-term and sustained IOP increases associated with anti-VEGF intravitreal injection therapy are of a real clinical concern [13] .…”
Section: Resultsmentioning
confidence: 99%
“…The use of intravitreal antiangiogenic agents has assumed increasing importance and worldwide application in various vitreoretinal pathologies. Recent evidence suggests that both short-term and sustained IOP increases associated with anti-VEGF intravitreal injection therapy are of a real clinical concern [13] .…”
Section: Resultsmentioning
confidence: 99%
“…Wehrli et al [14] reported that a sustained IOP elevation or 1 IOP elevation exceeding 26 mm Hg occurred in 1 eye of 104 (1%) after IVR injections without paracentesis during 2 years of follow-up. Menke et al [15] reported that the mean IOP was elevated significantly by 0.8 ± 3.1 mm Hg after IVR injections without paracentesis (p < 0.0001). The prevalence of sustained IOP elevations was lower in the current than in previous studies [12,13,14] and the highest mean IOP during the follow-up period was not significantly elevated from baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of sustained IOP elevations in patients with glaucoma have varied widely in previous studies [12,13,14,15]. Wehrli et al [14] also found no patients with AMD and glaucoma who developed a sustained IOP elevation or had an IOP elevation that exceeded 26 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations